A new species of planthopper in the genus Myconus (Hemiptera: Auchenorrhyncha: Fulgoroidea: Achilidae) from the Los Angeles Cloud Forest, Costa Rica - Echavarria, Marco A. Zumbado; Barrantes, Edwin A. Barrantes; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2022)
Recent survey work in Costa Rica has resulted in the discovery of a wide variety of undescribed species of planthoppers in the families Derbidae and Cixiidae. During a light trapping event in the Los Angeles cloud forest, a large planthopper was collected and determined to belong to the genus Myconus in the family Achilidae. Herein, the novel taxon is described with accompanying molecular data for the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and histone 3 (H3) gene and an updated key for the New World Myconus is provided.